Measurement properties of performance-based measures to assess physical function in knee osteoarthritis: A systematic review. (November 2022) - Chen, Hongbo; Wang, Cui; Wu, Junhui; Wang, Mengying; Wang, Siyue; Wang, Xiaowen; Wang, Jiating; Yu, Huan; Hu, Yonghua; Shang, Shaomei
Objective: To systematically review the measurement properties of performance-based measures to assess physical function in people with knee osteoarthritis. Data sources: PubMed, Web of Science, Embase, Scopus, CINAHL, and PsycINFO were searched in May 2022. Methods: This study was conducted in accordance with the guidelines recommended by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis. Clinical trials on the psychometric properties of performance-based tools for measuring physical function in people with knee osteoarthritis were included. Two reviewers independently rated measurement properties using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN). "Best evidence synthesis" was made using COnsensus-based Standards for the selection of health Measurement INstruments outcomes and the quality of findings. Results: Thirty-six out of 3425 publications were eligible for inclusion. Thirty-two performance-based measures were evaluated including 26 single-activity measures and 6 multi-activity measures. Measurement properties evaluated included internal consistency (2 measures), reliability (23 measures), measurement error (20 measures), hypotheses testing for construct validity (22 measures), and responsiveness (23 measures). On balance of the limited evidence, the walk 40 m fast-paced test and 6-minute walking test were the best rated walking tests. The 30-second chair stand test and timed up and go test were the best rated sit-to-stand tests. The Performance Tests Measures and Physical Activity Restrictions may be the suitable multi-activity measures for knee osteoarthritis. Conclusions: Further good quality research investigating the measurement properties, and in particular, the measurement error of performance-based measures in patients with knee osteoarthritis is needed.